TEACHING CULTURE IN ESP CLASSES - Islomova, Tohira (Журнал иностранных языков и лингвистики, 2021)
While language and culture are generally recognized to be intimately linked, English for Specific Purposes has typically been seen as “a cultural”. This article is about cultural information is a necessary component of any ESP course and that a contrastive-comparative approach can help the learner in appropriating other cultures.